PRINCIPLES OF IMPROVING AUDIT ACTIVITY IN BUSINESS SUBJECTS - EXPERIENCE OF FOREIGN COUNTRIES - Rakhmatullaeva Nargiza Nuriddinovna (Web of Journals Publishing, 2023)
In the article, the principles of improving audit activity in business entities - the experience of foreign countries.
Keywords: auditing activity, foreign experience, management, economy.